Development Of High Fibre Volume Fraction Natural Fibre Composite - Sallehuddin, Uwaiz (Universiti Sains Malaysia, 2018)
Composite materials are generally known as modern environmental friendly material which have much more benefits and competitive advantage compared to traditional material. The application of composite materials is widely used in many large market like transportation, sport, power and energy. Composites are light in weight, compared to most woods and metals. Their lightness is important in automobiles and aircraft, for example, energy or fuel efficiency can be improved as weight reduce. Natural fibre including coir, palm, bamboo and wood fibre are prospective reinforcing materials their use until now has been more empirical than technical. Nowadays various of methods are used to produce composite such as wet hand lay-up, resin infusion, compression molding, filament winding, prepreg, and many more. For this study, closed compression molding is applied to fabricate glass fibre and natural fibre composite. Results show that high fibre volume fraction will contribute high tensile strength for both natural fibre and synthetic fibre. Fibre volume fraction is one of the vital parameter need to be considered in order to produce good composite. For synthetic fibre, fibre volume fraction be determine using acid digestion process or burn-off process. For natural fibre, it totally inapplicable to use burn-off process and it must be treated thoroughly using correct solvent to quantify final fibre volume fraction. Thus, for this study, the most suitable method to find fibre volume fraction of palm fibre is using dichloromethane.